2016
DOI: 10.1177/1358863x16666691
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and echocardiographic predictors of anatomic site and outcomes of surgical interventions for cardiogenic limb emboli

Abstract: We sought to determine if symptomatic cardiogenic limb emboli have a random distribution or if there are demographic or echocardiographic factors that predict site of embolization, limb salvage and mortality. Upper (UE) and lower extremity (LE) emboli were evaluated over a 16-year period (1996-2012). Demographic (age, gender, smoking, medical comorbidities) and echocardiographic data were analyzed to determine predictors of embolic site. All symptomatic patients underwent surgical revascularization. Limb salva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Landry et al 4 indicated in their article that in a new study were reported patients with upper extremity acute arterial thromboembolism have more AF when compared to patients with lower extremity acute arterial thromboembolism. Lorentzen et al 7 reported in their studies that AF-associated embolization is the most common cause of lower extremity and this is followed by upper limb ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Landry et al 4 indicated in their article that in a new study were reported patients with upper extremity acute arterial thromboembolism have more AF when compared to patients with lower extremity acute arterial thromboembolism. Lorentzen et al 7 reported in their studies that AF-associated embolization is the most common cause of lower extremity and this is followed by upper limb ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…It is indicated that nonvalvular AF is the most common form in the world and is usually seen in the elderly. 4 Wasilewska and Bierska 6 indicated in their article that in a new Mayo Clinic study it is reported that AF patients with peripheral emboli complications are significantly older. In our study, mean age of arterial thromboembolism patients associated with nonvalvular AF was found to be 70.75 AE 14.97 for lower extremity and 73.23 AE 15.58 for upper extremity, and it was observed to be compatible with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with upper extremity ALI are more likely to have atrial fibrillation (50%) as compared to the 29.8% of patients with lower extremity acute limb ischemia [ 6 ], while patients with lower extremity ALI had a higher percentage of aortic or mitral valvular disease or intracardiac thrombus [ 6 ]. Upper extremity emboli are more frequent in women and patients with atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Upper extremity emboli are more frequent in women and patients with atrial fibrillation. Lower extremity emboli are more frequent in the presence of valvular disease or intracardiac thrombus and are associated with increased 30-day limb loss and mortality [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 This single-center case series evaluated 161 patients with symptomatic ALI due to cardiogenic emboli, of which 56 affected the upper extremity and 105 the lower extremity. The authors present a descriptive analysis of embolic limb events and not of atherothrombotic ALI occurring in patients with PAD.…”
Section: The Current Studymentioning
confidence: 99%